2010
DOI: 10.1111/j.1399-3046.2010.01453.x
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in pediatric liver transplant recipients compared with other chronic disease groups

Abstract: This cross-sectional, multi-center cohort study compares the level of health-related quality of life (HRQOL) of pediatric liver transplant (LT) recipients to children with other chronic health conditions.Design and Methods-LT sample included 873 children who survived at least 12 months following LT. Six chronic disease samples were compiled from numerous studies, including over 800 patients with Juvenile Rheumatoid Arthritis (JRA), type 1 diabetes, cancer in remission, cardiac disease, end-stage renal disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
87
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 33 publications
(39 reference statements)
7
87
0
Order By: Relevance
“…However, studies comparing QoL across different health conditions were difficult to conduct. Most studies that adopted generic questionnaires such as CHQ or PedQL would thus examine patients of a specific health condition with healthy population samples in a single study and then compare other health conditions using the 23 We found that children aged 5-10 years with an isolated mental health problem appeared to be more affected in their QoL when compared with either normal or children with an isolated physical health problem. In particular, the scores in concepts that measured general behaviour and role functioning in emotions and behaviour were significantly lower.…”
Section: Discussionmentioning
confidence: 89%
“…However, studies comparing QoL across different health conditions were difficult to conduct. Most studies that adopted generic questionnaires such as CHQ or PedQL would thus examine patients of a specific health condition with healthy population samples in a single study and then compare other health conditions using the 23 We found that children aged 5-10 years with an isolated mental health problem appeared to be more affected in their QoL when compared with either normal or children with an isolated physical health problem. In particular, the scores in concepts that measured general behaviour and role functioning in emotions and behaviour were significantly lower.…”
Section: Discussionmentioning
confidence: 89%
“…39,40 The mean PedsQL scores for the constipated subjects aged >8 years in the present study are comparable with those reported by other studies of children with chronic constipation, 21,37,41 but worse than those reported for patients with type 1 diabetes, malignancies in remission, cardiac disease, and transplant recipients. 42 Families may receive reassurance regarding the relatively benign nature of functional constipation along with suboptimal medical and behavioral treatments. When functional constipation is treated ineffectively, over time fecal incontinence develops, drastically reducing quality of life for the child and family.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation could be perceptions by providers of lower quality of life among children on dialysis and high burdens placed on parents and caregivers. Although children with ESRD do report diminished HRQOL scores when compared with healthy controls, HRQOL scores for children after renal transplantation appear to be similar to children with other types of chronic diseases (58)(59)(60)(61)(62). Furthermore, it is not clear why future quality of life would result in withholding treatment for a newborn, but not a toddler or older child.…”
Section: (35-45) a 2007 North American Pediatric Renal Trials And Comentioning
confidence: 94%